How Does the Level of Sacral Resection for Primary Malignant Bone Tumors Affect Physical and Mental Health, Pain, Mobility, Incontinence, and Sexual Function?. Issue 3 (March 2016) - Phukan, Rishabh; Herzog, Tyler; Boland, Patrick J.; Healey, John; Rose, Peter; Sim, Franklin H.; Yazsemski, Michael; Hess, Kathryn; Osler, Polina; DeLaney, Thomas F.; Chen, Yen‐Lin; Hornicek, Francis; et al.
Abstract: Background: En bloc resection for treatment of sacral tumors is the approach of choice for patients with resectable tumors who are well enough to undergo surgery, and studies describe patient survival, postoperative complications, and recurrence rates associated with this treatment. However, most of these studies do not provide patient‐reported functional outcomes other than binary metrics for bowel and bladder function postresection. Questions/purposes: The purpose of this study was to use validated patient‐reported outcomes tools to compare quality of life based on level of sacral resection in terms of (1) physical and mental health; (2) pain; (3) mobility; and (4) incontinence and sexual function. Methods: Our analysis included 33 patients (19 men, 14 women) who had a mean age of 53 years (range, 22‐72 years) with a quality‐of‐life survey administered at a mean postoperative followup of 41 months (range, 6‐123 months). The majority of patient‐reported quality‐of‐life outcome surveys for this study were taken from the National Institute of Health's Patient Reported Outcome Measurement Information System (PROMIS) system. To assess physical and mental health, the PROMIS Global Items Survey with physical and mental subscores, Anxiety, and Depression scores were used. Pain outcomes were assessed using PROMIS Pain Intensity and Pain Interference surveys. Patient‐reported lower extremity function was assessed using the PROMIS Mobility Survey. Patient‐reported quality of life for sexual function was assessed using the PROMIS Sex Interest and Orgasm survey, whereas incontinence was measured using the International Continence Society Voiding and Incontinence scores and the Modified Obstruction and Defecation Score. Surveys were collected prospectively during clinic visits in the postoperative period. Patients were grouped by the level of osteotomy as determined by review of postoperative MRI or CT and half levels were grouped with the more cephalad level. This resulted in the inclusion of total sacrectomy (N = 6), S1 (N = 8), S2 (N = 10), S3 (N = 5), and S4 (N = 4). One‐way analysis of variance tests on means or ranks were used to conduct statistical analysis between levels. Results: Patients with more caudal resections had higher physical health (95% confidence interval [CI] total sacrectomy 36‐42 versus S4 50‐64, p < 0.001), less intense pain (95% CI total sacrectomy 47‐60 versus S4 28‐37, p < 0.001), less interference resulting from pain (95% CI total sacrectomy 58‐69 versus S4 36‐51, p = 0.004), higher mobility (95% CI total sacrectomy 24‐46 versus S4 59‐59, p = 0.002), and were more functionally able to achieve orgasm (95% CI S1 1‐1 versus S4 2.2‐5.3, p = 0.043). No difference was found for PROMIS Global Item Mental Health Subscore, Sex Interest, Sex Satisfaction, modified obstruction and defecation score, and International Continence Society Voiding and Incontinence although this could be the result of an inadequate sample size. Conclusions: Our analysis on patient‐reported quality of life based on the level of bony resection in patients who underwent resection for primary sacral tumor indicates that patients with higher resections have more pain and loss of physical function in comparison to patients with lower resections. Additionally, use of the PROMIS outcomes allows for comparisons to normative data. Level of Evidence: Level III, therapeutic study.